2019
DOI: 10.3917/rsg.297.0011
|View full text |Cite
|
Sign up to set email alerts
|

Le comportement des managers face au fait religieux

Abstract: L’objectif de cet article est de fournir une grille d’intelligibilité des réactions des managers confrontés à l’extériorisation des croyances ou des appartenances religieuses au travail. En appui sur une revue de littérature et sur la théorie du comportement planifié (I. Ajzen et M. Fishbein, 1980), nous proposons une typologie et un modèle explicatif des comportements adoptés pour conclure sur les limites de notre approche ainsi que sur ses apports pour la formation des managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Other studies focus on the behavior of managers regarding REW (Cintas et al , 2020; Guillet, 2020; Guillet and Brasseur, 2019), the role played by tensions experienced in work situations (Volia, 2020), and managerial strategies at the individual level that deal with religious issues at work (Hennekam et al. , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies focus on the behavior of managers regarding REW (Cintas et al , 2020; Guillet, 2020; Guillet and Brasseur, 2019), the role played by tensions experienced in work situations (Volia, 2020), and managerial strategies at the individual level that deal with religious issues at work (Hennekam et al. , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2018). Cintas et al (2020) included the crucial role played by three factors in the intention to seek accommodation for the REW: (1) organizational flexibility, (2) perceived consequences, and (3) the religiosity of the manager, which was also important for Guillet (2020). Some authors have shown that the religiosity of leaders had a positive influence on openness to religious diversity, but did so without making the link with postures toward REW (Cui et al.…”
Section: Literature Reviewmentioning
confidence: 99%